COLD-WORKED HARDWARE - N. M. Strizhak (Литьë и металлургия)
The different types of cold-worked accessory are examined in the article. The necessity of development of such type of accessory in the Republic of Belarus due to requirements of market is shown. High emphasis is placed on the methods of increase of plasticity of cold-worked accessory from usual mill of RUP and CIS countries.